RANCANGAN PEMBELAJARAN JARINGAN KOMPUTER MODEL DICK DAN CAREY BERBASIS MANAJEMEN LAYANAN INFORMATION TECHNOLOGY INFRASTRUCTURE LIBRARY (ITIL) - Sallu, Sulfikar -; Qammaddin, Qammaddin (Universitas Muhammadiyah Jakarta, 2021)
Computer Network Learning is one of the teaching and learning processes in the compulsory Computer Networking course in a study program in the computer science family. Dick and Carey designs are the general components of a learning material from the procedures that will be used in learning to produce the desired learning outcomes. Furthermore, Information Technology Infrastructure Library (ITIL) is one of the frameworks that is part of Service Management in IT governance to make it easier to evaluate IT services and to find out things that must be developed in that service. The purpose of this study was to produce a design concept in the ITIL-based dick and carey model of computer network learning design. The method used is a literature review that utilizes all available reference sources. The result achieved is the ITIL-based Dick and Carey model computer network course concept which will create a quality computer network learning design.